2009
DOI: 10.3181/0808-rm-252
|View full text |Cite
|
Sign up to set email alerts
|

The Autophagic Induction in Helicobacter pylori-Infected Macrophage

Abstract: Helicobacter pylori has developed several mechanisms to evade the intracellular killing after phagocytosis. In this study, we reported that some Taiwanese clinical isolated H. pylori can multiply in human monocytic cells, such as THP-1 or U937 cells, but not in murine macrophage Raw264.7 cells. After internalization, there was a 5- to 10-fold increment of re-cultivable H. pylori from the infected THP-1 cells at 12 hrs post infection. The dividing H. pylori was found in a double-layer vesicle, which is characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 37 publications
7
95
1
2
Order By: Relevance
“…The CagA-positive H. pylori clinical isolate strain HP238, the isogenic cagA mutant strain HP238 CagAm , and the standard strain ATCC43504 were obtained from the Dr. Jiunn-Jong Wu (Department of Medical Laboratory Science and Biotechnology, National Cheng Kung University) and exhibited according to previous studies (31). As compared with ATCC43504, which normally presents an EPIYA-ABCCC motif, the genomic sequences of the clinical isolate HP238 contain are currently under investigation.…”
Section: Bacterial Strains and Culture Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CagA-positive H. pylori clinical isolate strain HP238, the isogenic cagA mutant strain HP238 CagAm , and the standard strain ATCC43504 were obtained from the Dr. Jiunn-Jong Wu (Department of Medical Laboratory Science and Biotechnology, National Cheng Kung University) and exhibited according to previous studies (31). As compared with ATCC43504, which normally presents an EPIYA-ABCCC motif, the genomic sequences of the clinical isolate HP238 contain are currently under investigation.…”
Section: Bacterial Strains and Culture Conditionmentioning
confidence: 99%
“…HP238 with a genetic isogenic mutation of cagA (HP238 CagAm ) was used (31). Western blotting showed a lack of CagA expression in HP238…”
Section: The Virulence Factor Caga Mediates H Pylori Infection-inducmentioning
confidence: 99%
“…20 More recent data suggest that H. pylori can survive inside cells. Several studies have demonstrated that H. pylori can persist in hepatocytes and replicate in macrophages, bone marrow-derived dendritic cells, 32 and gastric epithelial cells in vitro, thus providing evidence for its role as facultative intracellular organism with the ability to reside, replicate, and successfully evade antibiotic therapy within host cells. 33 Recent in vivo studies have further strengthened the role of H. pylori as an intracellular pathogen in mice and humans.…”
Section: Helicobacter Pylori As Intracellular Pathogenmentioning
confidence: 99%
“…38 Recent findings suggest that H. pylori survives in the intracellular environment by manipulating phagosome and autophagosome maturation. 32,39 It has been shown that strains carrying s1 isoforms of VacA have a dual effect on autophagy by promoting it in initial phases of contact with epithelial cells, although prolonged exposure to the toxin results in the disruption of autophagosome maturation. 40 Mechanistic insights on the molecular pathways affecting autophagosome formation, maturation, and degradation, and how these are manipulated by H. pylori are given in several recent publications.…”
Section: Helicobacter Pylori As Intracellular Pathogenmentioning
confidence: 99%
“…For bacteria unable to escape phagosomes after infection, such as M. tuberculosis and H. pylori, bacteria-containing phagosomes are sequestered by or fused with autophagosomes to form double-membrane or multimembrane compartments (Fig. 1, mode E) (16,21). Bacteria such as S. flexneri and L. monocytogenes that have escaped the phagosome to the cytosol can be engulfed by autophagosomes directly (Fig.…”
Section: Yersinia Pseudotuberculosismentioning
confidence: 99%